Progress of Analytical Techniques and Application of Triple Oxygen Isotopes in Dissolved Oxygen - Hongmin ZHENG; Xijie YIN; Haili YANG; Zijun WU (Journal of Isotopes)
Oxygen is one of the essential elements in Earth's ecosystem，with stable isotopes including δ16O，δ17O，and δ18O. The composition of oxygen stable isotopes (δ17O，δ18O) exhibits different fractionation patterns in various biogeochemical reactions，making them useful as tracers for biogeochemical cycles. The stable isotopes of dissolved oxygen (DO) in water bodies can be used to trace water mass mixing and the source-sink balance of oxygen elements. Compared to 18O，17O has a lower natural abundance and is highly susceptible to air interference during sample preparation and mass spectrometry analysis. Currently，research on δ17O is still quite limited. With the continuous development of dual-inlet mass spectrometry technology，δ17O can now be accurately measured，but the preparation process is time-consuming and labor-intensive. Continuous flow injection mass spectrometry offers higher efficiency but suffers from reduced precision due to unavoidable air interference. Combining the different fractionation patterns of δ17O and δ18O (TOI) in biological and chemical processes provides a new approach for estimating primary productivity in water bodies，avoiding errors in traditional methods. Additionally，ancient atmospheres preserved in ice cores can be used to infer paleoclimate evolution processes. The triple oxygen isotopes are increasingly being recognized for their value in fields such as ecology，environmental science，climatology，and marine science. This paper reviews the recent advancements in DO stable isotope analysis techniques in water bodies，introduces the current research and developments of triple oxygen isotopes in primary productivity estimation and paleoclimate evolution，and discusses future directions and trends for triple oxygen isotopes.